Drug Addiction Intervention for Adolescents with Religious Spirituality and Biofeedback - Salam, Urme; Muhammad Nubli, Abdul Wahab (Biofeedback Federation of Europe, 2014)
Religious spirituality (taubah, zikir and holy Quran recitation) and biofeedback devices (GSR & HRV) play a vital role in drug addiction treatment among teenagers. This study explored the effect of religious faith, spirituality and biofeedback in 36 drug addicted school students (aged13-19) of Kuantan, Pahang in Malaysia. Participants were randomly assigned either to a training group (n = 18) or control group (n = 18). Religious spirituality significantly help to reduce the drug addiction in the active training group (2 (4) = 34.359, p < 0.001, but not in the control group (2 (4) = 2.322, p >0.05. It was observed that high levels of religious faith and spirituality significantly effects to intervene the adolescents from addiction. Survey data indicate that high levels of religious faith and spirituality were closely related with positive life orientation, better perceived social assistance and lower levels of depression, anxiety and stress. The findings of this study confirmed that the effect of religious treatment was related to physiological change. Therefore this study represents the greatest self-report research to assess the relationship between religious faith and spirituality to recover the drug addiction through GSR and HRV biofeedback devices.